Perancangan Sistem Data Keuangan dan Pendaftaran Member pada Vanlino GYM Menggunakan Visual Basic 2010 - Haris Tehuayo; Ahmad Martani; Ayu Lestari Perdana (PT FORMOSA CENDEKIA GLOBAL, 2022)
Designing a Financial Data System and Member Registration at Vanlino Gym Using Visual Basic 2010. This study aims to design and test a financial data system and member registration at Vanlino Gym using Visual Basic 2010. This study uses the type of research and development (Research and Development). . The results of this study indicate an information system at Vanlino Gym in which there is information on prospective member profiles, member data, transaction data, category data and cashier data making transactions. Implement a member data information system at Vanlino Gym by installing this application on the admin computer so that it runs according to the results of the information system design that has been created and displays all transaction data and Vanlino Gym members on the member data menu.